Improving mechanical properties of recycled polypropylene-based composites using TAGuchi and ANOVA techniques - Zheng, Yitao; Gu, Fu; Ren, Yanru; Hall, Philip; Miles, Nicholas J. (Elsevier, 2017)
This study was aimed at optimising the composition of recycled plastic based composite for improving mechanical performance. The fractions of virgin polypropylene (vPP), talcum powder (talc) and maleic anhydride grafted polypropylene (MAPP) were selected as controllable factors. Taguchi L9 (33) orthogonal array (OA) was applied as an experimental design tool. Compositions were prepared by extrusion and injection moulding. The performance was measured and expressed in signal to noise (S/N) ratio. The S/N ratios were investigated by the Taguchi coupled analysis of variance (ANOVA) to determine optimal condition. The effectiveness and efficiency of the proposed approach was demonstrated through confirmation tests.